(untitled) (Jurnal Etika Kedokteran Indonesia, 2026)
ABSTRACT Introduction : Artificial Intelligence (AI) has become one of the most promising innovations in healthcare, particularly in the processing and interpretation of medical images. AI in radiology enhances diagnostic efficiency and accuracy by quickly processing medical images using techniques like machine learning. AI technology is applied in various imaging methods such as Magnetic Resonance Imaging (MRI) and CT scans (Computerized Tomography), serving as an assistive tool, not a replacement, to support radiologists in providing better patient care. Methodology : A literature search was conducted using PubMed and Google Scholar databases with the main keywords "Ethical consideration," "using AI," and "radiology." The selected articles were published within the last 10 years and written in English. Results and Discussion : Artificial Intelligence (AI) is a technology that mimics human intelligence and is applied across various fields, including healthcare. AI, which encompasses machine learning (ML) and transfer learning (TL), processes large-scale data (Big Data) and is used in medical image analysis, particularly in radiology, to enhance diagnostic accuracy. However, the use of AI in healthcare raises ethical concerns, especially regarding patient data privacy and security. Privacy models such as federated learning and differential privacy have been developed to safeguard data confidentiality. Conclusion : The application of AI in radiology presents ethical challenges, particularly related to patient data privacy and security. Therefore, strict standards, regulations, and oversight are necessary to maintain ethical AI use. While AI supports medical decision-making, radiologists remain responsible for patient care. Keywords : Ethical Consideration, Using AI, Radiology ABSTRAK Pendahuluan : Artificial Intelligence telah menjadi salah satu inovasi paling menjanjikan dalam dunia kesehatan, terutama dalam pemrosesan dan interpretasi gambar medis. ​​AI dalam radiologi meningkatkan efisiensi dan akurasi diagnosis dengan memproses gambar medis secara cepat menggunakan teknik seperti machine learning. Teknologi AI diterapkan dalam berbagai metode pencitraan seperti Magnetic Resonance Imaging (MRI) dan CT scan (Computerized Tomography scan), berperan sebagai alat bantu, bukan pengganti, yang mendukung radiolog dalam memberikan perawatan yang lebih baik kepada pasien. Metodologi : Pencarian literatur dilakukan menggunakan database Pubmed dan Google scholar dengan kata kunci utama “Ethical consideration”, “using AI”, “radiology”. Artikel yang digunakan dalam kurun waktu 10 tahun terakhir dan berbahasa Inggris. Hasil dan Pembahasan : Artificial Intelligence (AI) merupakan teknologi yang meniru kecerdasan manusia dan digunakan dalam berbagai bidang, termasuk medis. AI, yang mencakup machine learning (ML) dan transfer learning (TL), memproses data besar (Big Data) dan digunakan dalam analisis gambar medis, seperti pada radiologi, untuk meningkatkan akurasi diagnosis. Namun, penggunaan AI dalam medis menimbulkan kekhawatiran etis, terutama terkait privasi dan keamanan data pasien. Model privasi seperti federated learning dan differential privacy dikembangkan untuk menjaga kerahasiaan data. Kesimpulan : Penerapan AI dalam radiologi menimbulkan tantangan etis, terutama terkait privasi dan keamanan data pasien. Oleh karena itu, diperlukan standar, regulasi, dan pengawasan ketat untuk menjaga etika penggunaan AI. Meskipun AI mendukung keputusan medis, ahli radiologi tetap bertanggung jawab atas perawatan pasien. Kata kunci : Ethical Consideration, Using AI, Radiology